Parameters of Force Interaction of Elements the Wave Transmission with Intermediate Rolling Bodies in Geokhd's Transmission; Applied Mechanics and Materials; Vol. 682 : Innovation Technology and Economics in Engineering - Beglyakov V. Yu. Vyacheslav Yurievich (Material Science, Machining Technologies and Equipments in Mechanical Engineering, 2014)
Title screen